Istana Maimun : Potensi Pariwisata Bersejarah Sebagai Peluang Ekonomi Masyarakat Kota Medan - M Taufik Rahmadi; Chania Sirnip Belinda br Pakpahan (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
The most interesting thing in this era is tourism. Maimun Palace is one of the historical places or tours in Medan City. The objectives to be achieved in this study are 1) To find out the economic opportunities for the community in the Maimun Palace Tourism Park through Historical Tourism, 2) To find out what types of economic activities have the potential to improve the community's economy in the Maimun Palace Tourism Park, and 3) To find out the development strategy for Maimun Palace as an opportunity for the community's economy. This study uses a tourist attraction development method with a 4A approach, namely Attractions, Amenities, Accessibility, and Ancilliary. The results of the study show that Maimun Palace has the potential for historical tourism so that it can be an opportunity for the community's economy